2020
DOI: 10.1186/s13037-020-00257-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of surgical management of high grade blunt splenic injuries in adult trauma patients: a 5-year retrospective cohort study from an academic level I trauma center

Abstract: Backgrounds Splenic injury accounts for 40% of all injuries after blunt abdominal trauma. Blunt splenic injury in hemodynamically unstable patients is preferably treated by splenectomy. Nowadays hemodynamically stable patients with low grade splenic injuries are mostly treated by non-operative management (NOM). However no consensus exists about the management of high grade splenic injuries in hemodynamically stable patients. Therefore the aim of this study was to analyze patients with high grade s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
1
6
0
6
Order By: Relevance
“…From our experience, patient selection may have an impact not only on the rate of failure of NOM, but the mortality rate associated with it. Nowadays, the presence of hemodynamic instability is considered the only absolute contraindication for NOM 13 . Ongoing research is needed to evaluate whether to treat the patient operatively or with selective NOM, potentially leading to reduced LOS.…”
Section: Discussionmentioning
confidence: 99%
“…From our experience, patient selection may have an impact not only on the rate of failure of NOM, but the mortality rate associated with it. Nowadays, the presence of hemodynamic instability is considered the only absolute contraindication for NOM 13 . Ongoing research is needed to evaluate whether to treat the patient operatively or with selective NOM, potentially leading to reduced LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Em decorrência do trauma sofrido associado a comorbidades prévias, os pacientes politraumatizados podem desenvolver um quadro clínico potencialmente mais grave, e o que se tem de mais prevalente é a hipotermia, acidose metabólica e coagulopatia e essa tríade em geral é o principal mecanismo de morte secundário ao trauma. (NIJDAM et al, 2020). Pela associação da extensão das lesões e a resposta endrocrino metabólica ao trauma, foi observado que o paciente apresenta maior mortalidade por falência metabólica do que a abordagem Brazilian Journal of Health Review, Curitiba, v.4, n.5, p. 23346 -23353 sep./oct.…”
Section: Desenvolvimentounclassified
“…Traumas penetrantes são causados basicamente por ferimentos com arma de fogo (PAF), e são responsáveis por uma parcela considerável de lesões na rotina do pronto atendimento, e também temos os ferimentos por arma branca (FAB) e nesse caso o órgão mais acometido é o fígado. (NIJDAM et al, 2020).…”
Section: Introductionunclassified
“…[10] However, staging is not always a determinant of surgery, instead, it is hemodynamic status and peri-operative intra-peritoneal bleeding that are the main indications for surgical intervention. [11] Other factors include the presence of comorbid conditions or other traumatic injuries. Patients who are hemodynamically unstable should be offered intravenous fluid bolus, those who do not respond well to fluids or transiently respond before deteriorating are considered as high-risk for underlying organ laceration, including splenic and liver trauma.…”
Section: Indications For Operative Interventionmentioning
confidence: 99%
“…Patients who are hemodynamically unstable should be offered intravenous fluid bolus, those who do not respond well to fluids or transiently respond before deteriorating are considered as high-risk for underlying organ laceration, including splenic and liver trauma. [11] Research has reported a risk of splenic rupture in patients infected with the coronavirus-19 disease, this is best managed with emergency surgery. In such infected patients with sudden severe abdominal pain, a low threshold for entering the operating theatre is practiced.…”
Section: Indications For Operative Interventionmentioning
confidence: 99%